A novel series of indazole-/indole-based glucagon receptor antagonists. Issue 19 (1st October 2015) - Lin, Songnian; Zhang, Fengqi; Jiang, Guoqiang; Qureshi, Sajjad A.; Yang, Xiaodong; Chicchi, Gary G.; Tota, Laurie; Bansal, Alka; Brady, Edward; Trujillo, Maria; Salituro, Gino; Miller, Corey; et al.
Graphical abstract